Gambaran Kejadian Malaria Pada Ibu Hamil di Rumah Sakit Umum Daerah Kabupaten Boven Digoel Papua - Halmina Ilyas; Serly Serly (An Idea Health Journal, 2021)
In malaria endemic areas, pregnant women are more susceptible to infection with malaria parasites than non-pregnant women. The World Health Organization (WHO) in 2014 estimated that 10,000 maternal deaths each year were associated with malaria infection during pregnancy. The aim of the study was to describe the incidence of malaria in pregnant women at the Boven Digoel District General Hospital, Papua. Methods This research uses a descriptive type of research. Samples were taken as many as 92 pregnant women who were taken by accidental sampling. Collecting data by using a questionnaire sheet. Data analysis was carried out univariate and bivariate. The results showed that from 78 pregnant women who were positive for malaria, most of them suffered from anemia as many as 51 people (65.4%) and 27 people did not suffer from anemia (34.6%). For the incidence of abortion from 78 pregnant women who were positive for malaria, most of them did not experience an abortion as many as 62 people (79.5%) and 16 people had an abortion (20.5%). For the habit of being out of the house at night, from 78 pregnant women who were positive for malaria, most of them were always outside at night as many as 41 people (52.6%) and 37 people (47 people) were not out of the house at night. ,4%). The conclusion of this study, the description of the incidence of malaria in pregnant women mostly suffer from anemia, do not have abortions and are always outside the house at night. The advice that can be given is that malaria in pregnant women must be eradicated immediately so that the MCH program made by the government can be successful and the health of pregnant women can be maintained